The rise of conductive copper inks: challenges and perspectives. (March 2020) - Li, Wanli; Sun, Qingqing; Li, Lingying; Jiu, Jinting; Liu, Xu-Ying; Kanehara, Masayuki; Minari, Takeo; Suganuma, Katsuaki
Graphical abstract: Highlights: Mainstream strategies for avoiding oxidation of Cu inks are reviewed. Cu precursor inks are elaborated as an effective strategy. Efficient sintering methods and related sintering mechanisms are summarized. Strategies for the improvement of the reliability of Cu patterns are summarized. Challenges and future prospects for Cu inks are provided. Abstract: Conductive inks have gathered increasing attention in the fabrication of next-generation electronic devices because of their prominent compatibility and producibility. Recently, copper (Cu) inks as the new darling of conductive inks are studied extensively because Cu possesses an intrinsic high conductivity (comparable to the highest conductive metal, silver (Ag)) but an ultralow cost (about 1% the cost of Ag) with abundant reserves. However, the low resistance of Cu towards oxidation results in three issues, in aspects of the synthesis of stable Cu inks, the fabrication of highly conductive Cu patterns, and the long-term reliability of Cu-based electronic performances, which hinders the application prospect of Cu inks in the next-generation electronic devices. Herein, this review summaries the advanced developments of Cu inks in term of formulations, sintering methods, and long-term reliability. The mainstream strategies for avoiding oxidation and improving the stability of Cu inks and Cu patterns are described, while the efficient sintering methods and related sintering mechanisms are analyzed. The effect of ink formulations and sintering methods on the conductivity of Cu patterns on various substrates are also discussed. In addition, the strategies for the improvement of long-term reliability of Cu patterns and their application in various devices are summarized and forecasted. Finally, the challenges and future prospects for Cu inks are involved as well.